Analisis Kekuatan Bahan Pipa Ijuk Semen Berbasis Serat Ijuk Yang Bernilai Ekonomis - Heri Sujatmiko (Universitas Teuku Umar, 2020)
AbstractWater is the main support for human survival. Most frequently, the emergence ofproblems in the community environment is caused by the lack of clean water. Lack of cleanwater supply often occurs in rural areas, where residents cannot afford to buy PVC pipes andlarge pipes for water distribution, so we conducted a study and developed a simple method ofmaking pipes, using materials that are easily available, and can be made by ourselves, which isa pipe with a mixture of palm fiber and cement. Using cement fibers should apply operationalprocesses to water with good quality.